EFEKTIFITAS PENAMBAHAN TEPUNG DAUN BAMBU PETUNG (Dendrocalamus asper) PADA PRODUKSI SUSU INDUK UNTUK MENGURANGI MORTALITAS ANAK KELINCI PRASAPIH - Mubarak Akbar; Dyah Nurul Afiyah; Hyankasu Adeca Pandyambika Fatista Sitaningtyas (Universitas Islam Kadiri, 2019)
The objective of the study was to determine the effect of bamboo leaf on influence rabbit doe milk production and kits mortality during 3 weeks first of age. Thirty six does aged 6-12 months, divided into three blocks, of four treatment diets, were used in our replicity. The diet treatments used bamboo leaf meal: 0% (P0), 2% (P1), 4% (P2), and 6% (P3). The parameters observed were: dry matter intake, doe’s milk production, kits mortality, and kit as level: body weight gain. The results showed that supplementation of bamboo leaf meal increased (P < 0,05) dry matter intake whereas doe milk production, kits mortality, body weight gain of kits during 3 weeks experiment were not affected by bamboo leaf meal supplementation